Method for rapidly preparing small-aperture alpha alumina ultrafiltration membrane through photo-thermal reinforcement
By doping photothermal conversion materials in alumina material and controlling the heat treatment conditions, the problem of low energy utilization efficiency of alumina in near-infrared radiation heat treatment is solved, and a method for rapid preparation of high-performance α alumina ultrafiltration membrane is realized.
Patent Information
- Application Number
- CN202510107049.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-01-22
AI Technical Summary
Alumina materials have low energy utilization efficiency in near-infrared radiation heat treatment, which leads to difficult phase transformation. Conventional heat treatment leads to excessive grain growth and pore aggregation, reducing separation and permeability.
By doping photothermal conversion materials during sol preparation, the light energy utilization efficiency of alumina is improved, and temperature and time are controlled during the heat treatment process to avoid pore aggregation, and a high separation accuracy and high permeability α alumina ultrafiltration membrane is prepared.
It realizes the rapid preparation of high-performance α-alumina ultrafiltration membrane with small pore size, narrow distribution and thin layer thickness structure at low temperatures, improving separation accuracy and permeability, and shortening the heat treatment cycle.
Smart Images

Figure CN119733391A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for rapidly preparing an alpha alumina ultrafiltration membrane with high separation accuracy and high permeability having a small pore size, narrow distribution and thin layer thickness structure by strengthening the energy utilization efficiency of alumina materials in rapid heat treatment and reducing the energy barrier required for phase change, belonging to the technical field of ceramic ultrafiltration membranes. Background Art
[0002] Membrane separation has become an important method for separating key active components in biomanufacturing due to its good bioaffinity. Due to the complexity of biological systems, key active components with specific molecular weight distribution require membrane materials with high separation accuracy and high permeability for extraction. Currently, a large number of research works have been devoted to improving pore uniformity and enhancing membrane hydrophilicity by optimizing heat treatment conditions, surface grafting modification and other methods, in order to prepare high-performance ceramic membrane materials suitable for the biomedical field.
[0003] Ceramic membranes are usually prepared as separation materials with specific pore structures through heat treatment. In the conventional heat treatment process, the heat treatment temperature and cycle required for the phase change of ceramic materials are high, which not only promotes the crystal phase transformation, but also promotes excessive grain growth and pore agglomeration. Although ceramic ultrafiltration membranes with smaller average pore sizes can be prepared by optimizing precursors, element doping, introducing crystal seeds, and interlayer interactions, the problem of wide pore size distribution still limits its separation efficiency and application space.
[0004] The near-infrared radiation heat treatment process is a surface rapid heat treatment technology that can prepare small-pore-size, narrow-distribution ceramic ultrafiltration membranes within a few seconds to a few minutes, and is often used to prepare non-phase-change membrane materials. However, alumina has a low efficiency in utilizing near-infrared radiation energy, and α-alumina is a material produced by high-temperature phase change, which makes it more difficult for α-alumina to change phase during rapid heat treatment. Extending the treatment time and increasing the heat treatment temperature will lead to excessive grain growth, particle agglomeration and pore agglomeration, resulting in a decrease in both separation performance and permeability performance.
[0005] Therefore, how to improve the energy utilization efficiency of alumina in near-infrared radiation heat treatment and produce ceramic ultrafiltration membranes with high selectivity and permeability in a short time and at low heat treatment temperature is an urgent problem that needs to be solved in this field. Summary of the invention
[0006] The purpose of the present invention is to solve the problem of phase transition difficulty caused by low near-infrared radiation energy utilization efficiency of aluminum oxide materials. The particle size and light response degree of the sol are regulated by controlling the type and amount of element doping in the sol preparation process; the crystal phase transition, grain growth and pore agglomeration process are controlled by controlling parameters such as the heat treatment temperature during the heat treatment process. Thus, a method for rapidly preparing a ceramic membrane with high separation accuracy, high permeability and specific crystal form at low temperature is provided.
[0007] A method for rapidly preparing a small-pore alpha-alumina ultrafiltration membrane by photothermal enhancement comprises the following steps:
[0008] Step 1, preparing nanoscale composite sol;
[0009] Step 2, applying the composite sol obtained in step 1 to the surface of a ceramic support; performing near-infrared heat treatment on the ceramic membrane to obtain a ceramic membrane;
[0010] The composite sol contains light-to-heat conversion material.
[0011] In step 1, the average particle size of the composite sol is 1-10 nm, the minimum particle size is 1-3 nm, and the maximum particle size is 10-25 nm.
[0012] The light-to-heat conversion material is one or more of narrow-bandgap metal oxides, carbon materials or organic substances.
[0013] In step 1, the preparation method of the composite sol comprises the following steps:
[0014] 4. Mixing the photothermal conversion material and the first solvent and heating them under reflux to obtain a dopant mixed solution;
[0015] 5. Adding an inorganic salt or alcohol salt of aluminum to the second solvent and stirring to form an aluminum salt mixed solution;
[0016] 6. Add the dopant mixed solution to the aluminum salt mixed solution obtained in step ②, add a peptizing agent or a chelating agent, and reflux.
[0017] After further aging, a composite sol is obtained.
[0018] The narrow bandgap metal oxide of the photothermal conversion material described in step ① includes one or a combination of two or more oxides of iron, cobalt, nickel, manganese, copper, titanium, silver, cerium, and platinum;
[0019] The carbon material includes one or a combination of two or more of carbon quantum dots, graphite, graphyne, graphene, graphene oxide, carbon nanotubes, and fullerene;
[0020] The organic matter includes one or a combination of two or more of cretone acid derivative structure, indocyanine green, Prussian blue, thiadiazole derivatives, porphyrin ring, polyaniline, polypyrrole, polythiophene, and polydopamine;
[0021] The photothermal conversion material is 5-15% by mole of aluminum salt;
[0022] The first solvent and / or the second solvent described in step ① include one or a combination of two or more of methanol, ethanol, propanol, isopropanol, n-butanol, and isobutanol.
[0023] The reflux temperature in step ① is 50-100° C. and the time is 0.5-3 h.
[0024] The inorganic salt and alkoxide described in step ② include one or a combination of two or more of aluminum nitrate, aluminum chloride, aluminum sulfate, aluminum sulfide, diethyl aluminum phosphate, aluminum acetate, aluminum citrate, aluminum propoxide, and aluminum butoxide; the dosage ratio of the inorganic salt or alkoxide of aluminum to the second solvent is 0.05-0.3 mol: 1-5 ml;
[0025] The peptizing agent or chelating agent described in step ③ includes one or a combination of two or more of nitric acid, hydrochloric acid, sulfuric acid, citric acid, acetic acid, and oxalic acid, and the molar ratio of the peptizing agent or chelating agent to the aluminum salt is 0.5-3:1.
[0026] In the step 2, the composite sol is applied to the surface of the ceramic support by one or more of the following methods: immersion pulling, spin coating, spraying, plasma sputtering, and vapor deposition. In the step 2, the heating rate of the near-infrared heat treatment is 600-3000°C / min, the maximum temperature is 800-900°C, and the insulation time is 0-60s. The ceramic support of the ceramic membrane is a porous ceramic material with an average pore size of 50-200nm.
[0027] A ceramic membrane is obtained by the preparation method.
[0028] The application of the ceramic membrane in liquid filtration.
[0029] A method for reducing the pore size of a ceramic ultrafiltration membrane or narrowing the pore size distribution comprises the following steps:
[0030] The ceramic ultrafiltration membrane is prepared by polymerizing sol, and the polymerizing sol contains a photothermal conversion material. During the calcination process of the ceramic membrane, a near-infrared heat treatment is performed.
[0031] Beneficial Effects
[0032] The present invention aims to solve the problem that alpha alumina has difficulty in phase change due to low light energy conversion efficiency under rapid heat treatment using near-infrared radiation as an energy source. The light energy utilization efficiency of alumina is improved by doping with photothermal strengthening materials, the pore agglomeration problem caused by long-term high temperature in conventional heat treatment is avoided, and the heat treatment cycle of alumina ultrafiltration membrane is greatly shortened. The doped second phase can also reduce the phase change activation energy through seed and pinning effects and further inhibit the pore agglomeration phenomenon caused by sintering, thereby quickly preparing a highly selective and highly permeable alpha alumina ultrafiltration membrane with a microstructure with a small average pore size and a narrow pore size distribution. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1:Composite sols with different element doping amounts. A. Visible light spectrum, B. Digital photo of sol, C. Change of sol potential, D. Change of sol particle size;
[0034] Figure 2 :Energy bands of composite gel and alumina gel and changes in absorbance to near-infrared radiation.
[0035] Figure 3 : XRD patterns of undoped alumina sol under different rapid thermal treatment conditions.
[0036] Figure 4 : XRD patterns and grain size evolution of doped sol under different rapid thermal treatment conditions.
[0037] Figure 5 : Electron micrographs of the surface and cross section of element-doped α-alumina ultrafiltration membrane.
[0038] Figure 6 :Comparison of properties of α-alumina films prepared by two sols. A. Pure water contact angle, B. Pure water penetration rate.
[0039] Figure 7 :Comparison of the properties of α-alumina membranes prepared from two sols. A. Dextran molecular weight cut-off, B. Pore size distribution. DETAILED DESCRIPTION
[0040] 1. Preparation of sol:
[0041] In the preparation process of the following α-alumina ultrafiltration membrane, two sols were used to prepare the α-alumina ultrafiltration membrane, which were named Sol-1 and Sol-2 respectively. The specific preparation process is as follows:
[0042] Sol-1:
[0043] According to the polymerization sol preparation process in the prior art [Shi W, Yang C, Qiu M, et al. A new method for preparing α-alumina ultrafiltration membrane at low sintering temperature [J]. Journal of Membrane Science, 2022, 642: 119992.], the preparation method of the sol is to add a small amount of ethanol to the precursor aluminum sec-butoxide, and then mix the solution with ethanol and acetic acid, heat and stir to form an amorphous alumina sol, and the chemical reaction of the alumina sol is manifested as a hydrolysis and condensation process of aluminum sec-butoxide controlled by an esterification reaction.
[0044] The specific preparation method is as follows:
[0045] 3 ml of ethanol and 0.1 mol (24.6 g) of aluminum sec-butoxide were stirred vigorously to form a uniform solution. Then, the prepared solution was added to 250 ml of ethanol at 70°C and kept warm for 1 hour. Subsequently, 0.15 mol (8.6 g) of acetic acid was added and the reflux and stirring conditions were kept constant for 1 hour. After the sol was cooled to room temperature, it was aged for 12 hours.
[0046] Sol-2:
[0047] The specific preparation method is as follows:
[0048] 3 ml of ethanol and 0.1 mol (24.6 g) of aluminum sec-butoxide were stirred vigorously to form a uniform solution A. 10 mol.% (compared to the amount of aluminum sec-butoxide) of ferric nitrate was added to 250 ml of ethanol, stirred and heated to 70°C to form a solution B. Then, the prepared solution A was added to solution B and kept warm for 1 hour. Subsequently, 0.15 mol (8.6 g) of acetic acid was added, and the reflux and stirring conditions were kept constant for 1 hour. After the sol was cooled to room temperature, it was aged for 12 hours.
[0049] 2. Sol and powder characterization:
[0050] The macroscopic color, absorption characteristics, potential value and particle size distribution of the sol prepared by the two methods are shown in Figure 1 middle. Figure 1 A and B are the changes in the optical properties of the sol. As the doping amount of the element increases, the visible light absorption intensity of the sol increases, which is manifested as a change in color from colorless, yellow, red, brown to black. Although the absorbance is enhanced with the increase in the doping amount of the element, the sol potential decreases with the increase in the doping amount of the element, and the sol tends to be unstable ( Figure 1 C). It is manifested in the particle size distribution ( Figure 1 In D), the sol particle size becomes larger and wider with the increase of the element doping amount. When the doping amount is 0-10 mol.%, the sol particle size hardly changes and shows good photoresponse thermal properties.
[0051] Sol-1 and Sol-2 (10 mol.% Fe element) were dried, and the energy gap and near-infrared absorption spectra of the obtained gel powders were as follows: Figure 2 As shown. The near-infrared spectrum peak shows that the near-infrared light absorption rate of the doped material is improved and the absorption range is enhanced. The sol doped with the photothermal enhancement material also shows a smaller energy gap. These characteristics mean that the material can be activated at a lower energy input and can receive more energy from near-infrared radiation.
[0052] Based on near-infrared radiation rapid annealing furnace (power: 5.4kW, short-wave near-infrared radiation wavelength range: 0.8μm~1.4μm) at 10℃·s -1Sol-1 was heat treated with different heating rates and holding times. Figure 3 It can be seen that no matter how long the heat treatment time is extended, alumina has not completed the transformation to α-alumina (the position indicated by the dotted line is the characteristic peak position of α-alumina) at temperatures of 1050°C and below. This indicates that the light energy utilization efficiency of pure alumina is low, and it is difficult to change the energy input by extending the time, and it is impossible to cross the phase change energy barrier.
[0053] At 10℃·s -1 Sol-1 and Sol-2 (10 mol.% Fe element) were heat treated at a heating rate of 1000 s and a holding time of 30 s, respectively named Powder-1 and Powder-2. Their X-ray diffraction spectra are shown in Figure 3 , Figure 4 As shown. The unreinforced alumina sol can only undergo a partial phase change at 1050°C, while the doped and reinforced alumina sol has completely transformed at 850°C and exhibits a smaller grain size. Compared with the preparation process of undoped sol, the sol prepared by the new process has a smaller particle size and higher reaction activity. The energy utilization efficiency of light energy is improved after photothermal strengthening. At the same time, the environment introduced by the second phase reduces the activation energy required for the formation of α-alumina, thereby reducing the complete conversion temperature of α-alumina by 200°C and completing the heat treatment process within 2 minutes.
[0054] 3. Membrane structure optimization:
[0055] In order to study the effect of rapid thermal treatment on membrane structure, the complete gel layer prepared by dip coating was calcined based on conventional thermal treatment and rapid thermal treatment to prepare α-alumina ultrafiltration membrane. The support body used a zirconium oxide membrane with a molecular weight cutoff of about 300 kDa and a pore size of about 30 nm. Before sol coating, no additives were added to the sol and no further treatment was performed. Figure 5 A and B are the surface and cross section of the α-alumina membrane prepared by the enhanced process. The membrane surface is complete and smooth, and the thickness is relatively thin, while the surface of the α-alumina ultrafiltration membrane prepared by the conventional heat treatment process is rougher and thicker.
[0056] In order to understand the effect of element doping on the properties of the membrane surface, the hydrophilicity of the membrane materials was characterized and compared by surface contact angle test. Figure 6 The test results for hydrophilicity characterization. The Fe-doped alumina membrane exhibits a lower surface contact angle and faster water permeability, which indicates that it may have better performance in permeability, membrane surface cleaning, and anti-fouling.
[0057] 4. Optimization of interception performance:
[0058] In order to understand its separation performance, its retention performance of dextran complex solution was studied ( Figure 7The retention of dextran by undoped α-alumina membrane (conventional heat treatment) and element-doped α-alumina membrane is compared with the pore size distribution obtained by retention calculation. Figure 7 As shown. The molecular weight cutoffs of Fe-doped α-alumina ultrafiltration membrane and undoped α-alumina ultrafiltration membrane for dextran composite solution at a retention rate of 90% are approximately 14kDa and 26kDa, and the corresponding average pore sizes are approximately 5nm and 8nm. From the undoped α-alumina ultrafiltration membrane prepared by conventional heat treatment to the Fe-doped α-alumina ultrafiltration membrane, the preparation cycle is shortened from 24h to less than 2min, the pore size becomes smaller, and the distribution becomes narrower.
Claims
1. A method for rapidly preparing a small-pore α-alumina ultrafiltration membrane by photothermal enhancement, characterized in that: The following steps are involved: Step 1, preparing nanoscale composite sol; Step 2, applying the composite sol obtained in step 1 to the surface of a ceramic support; performing a near-infrared radiation heat treatment on the ceramic film to obtain a ceramic film; The composite sol contains light-to-heat conversion material.
2. The method for rapidly preparing small-pore α-alumina ultrafiltration membrane by photothermal enhancement according to claim 1, characterized in that: In step 1, the average particle size of the composite sol is 1-10 nm, the minimum particle size is 1-3 nm, and the maximum particle size is 10-25 nm.
3. The method for rapidly preparing small-pore α-alumina ultrafiltration membrane by photothermal enhancement according to claim 1, characterized in that: The light-to-heat conversion material is one or more of narrow-bandgap metal oxides, carbon materials or organic substances.
4. The method for rapidly preparing small-pore α-alumina ultrafiltration membrane by photothermal enhancement according to claim 1, characterized in that: In step 1, the preparation method of the composite sol comprises the following steps: ① Mixing the photothermal conversion material with the first solvent and heating them under reflux to obtain a dopant mixed solution; ② Adding an inorganic salt or alcohol salt of aluminum to the second solvent and stirring to form an aluminum salt mixed solution; ③ Add the dopant mixed solution to the aluminum salt mixed solution obtained in step ②, add a peptizing agent or a chelating agent, reflux, and then age to obtain a composite sol.
5. The method for rapidly preparing small-pore α-alumina ultrafiltration membrane by photothermal enhancement according to claim 4, characterized in that: The narrow bandgap metal oxide of the photothermal conversion material described in step ① includes one or a combination of two or more oxides of iron, cobalt, nickel, manganese, copper, titanium, silver, cerium, and platinum; The carbon material includes one or a combination of two or more of carbon quantum dots, graphite, graphyne, graphene, graphene oxide, carbon nanotubes, and fullerene; The organic matter includes one or a combination of two or more of cretone acid derivative structure, indocyanine green, Prussian blue, thiadiazole derivatives, porphyrin ring, polyaniline, polypyrrole, polythiophene, and polydopamine; The photothermal conversion material is 5-15% by mole of aluminum salt; The first solvent and / or the second solvent described in step ① include one or a combination of two or more of methanol, ethanol, propanol, isopropanol, n-butanol, and isobutanol.
6. The method for rapidly preparing small-pore α-alumina ultrafiltration membrane by photothermal enhancement according to claim 4, characterized in that: The reflux temperature described in step ① is 50-100° C., and the time is 0.5-3 h; the inorganic salt and alkoxide described in step ② include one or a combination of two or more of aluminum nitrate, aluminum chloride, aluminum sulfate, aluminum sulfide, diethyl aluminum phosphate, aluminum acetate, aluminum citrate, aluminum propoxide, and aluminum butoxide; the dosage ratio of the inorganic aluminum salt or alkoxide to the second solvent is 0.05-0.3 mol:1-5 ml; the peptizing agent or chelating agent described in step ③ includes one or a combination of two or more of nitric acid, hydrochloric acid, sulfuric acid, citric acid, acetic acid, and oxalic acid, and the molar ratio of the peptizing agent or chelating agent to the aluminum salt is 0.5-3:
1.
7. The method for rapidly preparing small-pore α-alumina ultrafiltration membrane by photothermal enhancement according to claim 1, characterized in that: In the step 2, the composite sol is applied to the surface of the ceramic support by one or more of the following methods: immersion pulling, spin coating, spraying, plasma sputtering, and vapor deposition. In the step 2, the heating rate of the near-infrared radiation heat treatment is 600-3000°C / min, the maximum temperature is 800-900°C, the holding time is 5-60s, and the wavelength range is 0.8μm-1.4μm. The ceramic support of the ceramic membrane is a porous ceramic material with an average pore size of 50-200nm.
8. A ceramic membrane, characterized in that: Obtained by the preparation method according to any one of claims 1 to 8, the ceramic membrane has an average pore size of 4 to 10 nm.
9. Use of the ceramic membrane according to claim 9 in liquid filtration.
10. A method for reducing the pore size of a ceramic ultrafiltration membrane or narrowing the pore size distribution, comprising the following steps: preparing the ceramic ultrafiltration membrane by polymer sol, wherein the polymer sol contains a photothermal conversion material, and during the calcination process of the ceramic membrane, heat treatment is performed by near-infrared method.
Citation Information
Patent Citations
Method used for preparing small aperture ceramic films by metal doping
CN103463998A
Preparation method of high-flux and high-precision ceramic ultrafiltration membrane for oil removal and iron removal of high-temperature condensed water
CN105561803A
Preparation method of photo-thermal conversion ceramic membrane and method for treating degradation-resistant wastewater
CN110917898A
Anti-pollution ceramic membrane as well as preparation method and application thereof
CN113926321A
Preparation method of alpha-alumina ultrafiltration membrane with small pore diameter, narrow distribution and high permeability
CN118681417A
Cited By
Porous alumina ceramic, preparation method thereof, semiconductor vacuum chuck and application
CN120736918A